2024
DOI: 10.1109/tnnls.2022.3190671
|View full text |Cite
|
Sign up to set email alerts
|

GMILT: A Novel Transformer Network That Can Noninvasively Predict EGFR Mutation Status

Abstract: Noninvasively and accurately predicting the epidermal growth factor receptor (EGFR) mutation status is a clinically vital problem. Moreover, further identifying the most suspicious area related to the EGFR mutation status can guide the biopsy to avoid false negatives. Deep learning methods based on computed tomography (CT) images may improve the noninvasive prediction of EGFR mutation status and potentially Manuscript

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Our approach is also robust against human variance, which is high, as shown in our inter-rater consistency analysis. Finally, the current method focuses on modeling only the CT modality, whereas ideally, clinicians use a variety of information, such as smoking history and multiomics information (52,53) to better estimate the metastasis and malignancy of solid PNs. Aggregating such information in our modeling may further boost its diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach is also robust against human variance, which is high, as shown in our inter-rater consistency analysis. Finally, the current method focuses on modeling only the CT modality, whereas ideally, clinicians use a variety of information, such as smoking history and multiomics information (52,53) to better estimate the metastasis and malignancy of solid PNs. Aggregating such information in our modeling may further boost its diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, due to the inherent glioma nature of tumor heterogeneity and lesion boundary diffusion, quite a lot of noise mixed with information related to the IDH genotyping. Compared with CNN, the Transformer network was more prudent to the signal noise [ 37 , 38 , 39 ]. (ii) Hierarchical architecture spurred by the translation invariance advantage of CNN had the flexibility to model at various scales.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with radiomics model, the end-to-end deep learning method can extract high-order image features by using a self-learning strategy and does not require a precise annotated tumour boundary (Gong et al 2020). For a data-driven algorithm, a relatively large dataset must be collected to train the deep learning model (Wang et al 2019, Haim et al 2022, Zhao et al 2022. Previous deep learning studies have demonstrated promising performance in the risk prediction of lung cancer (Dong et al 2021, Gong et al 2021.…”
Section: Introductionmentioning
confidence: 99%